Zero-Dimensional Carbon Nanomaterials : Fundamentals and Applications - Solanki, Pratima R.; Singh, Ravindra Pratap (IOP Publishing, 2022)
This book covers the latest advances in the field of zero-dimensional nanomaterials, with a focus on carbon quantum dots (CQDs) and graphene quantum dots (GQDs).
Keywords: Materials science.; Nanostructured materials.; Quantum dots.; elektronické knihy; electronic books